Resisting the siren call of digitalisation - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
THE symbiotic relationship between music making and media technology is often under-appreciated by the public, who only see the so-called glamour and pomp of the entertainment industry.